Judicial Efficiency and Immigrant Entrepreneurs. (7th November 2017) - Falavigna, Greta; Ippoliti, Roberto; Manello, Alessandro
Abstract : Extensive research exists on the individual determinants of being an immigrant entrepreneur, concerning both social environment and human capital. However, the role of the judiciary has not been investigated yet. Analyzing more than 160, 000 new micro enterprises owned by immigrants, our paper aims to fill this gap by focusing on the relation between justice and immigrant entrepreneurship. Results show that judicial efficiency is one of the determinants of self‐employment, although some differences among immigrant groups are identified. Therefore, the study confirms the key role of judicial enforcement in promoting not only growth but also the integration of these new citizens.